ANALISIS KANDUNGAN INFORMASI ARUS KAS, KOMPONEN ARUS KAS, DAN LABA AKUNTANSI TERHADAP HARGA DAN RETURN SAHAM - Tjiptowati Endang Irianti (Jurnal Ekonomi dan Bisnis, 2009)
Accounting information is used by potential users, especially Investors to make necessaryeconomic decision. Earning and cash flow are some of the measure that show a firms successfulmanagement. Earning is useful for measuring a firms performance,and the cash flowinformation key measure of liquidity. Accounting information is not yet one of the fundamentalanalysis tools for trading in Indonesian Capital Market However, accounting information isnecessary for making important decisions in capital market. The objective of this study is toexamine the association of the information content of independent variables total cash flows,components of cash flows, and accounting income with stock price or stock return.As much 29 firms listed in Jakarta Stock Exchange (JSX) were taken as a sample using purposivesampling method. Data from audited financial statements in year 2006 and 2007 weretaken from Indo-exchange files. The statistic method used to test hypothesis is a liner multipleregression Two models were considered: levels and return models.The statistical result of this shows that accounting income, cash flows and components ofcash flows are significantly associated with stock price in levels model, in contrast,the resultof this study shows that all independent variables (total cash flows, components of cashflows,and accounting income) are not associated with stock return in return model, exceptcash flows operation is significantly associated with stock return.Keywords : Information content, Cash Flows, Component of cash flows, Levels model, Return model